2005
DOI: 10.2486/indhealth.43.337
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysically Determined Asymmetrical Lifting Capabilities for Different Frequencies and Containers

Abstract: Back injuries to the lifters caused by lifting remain a common occurrence not only in developed countries, but also in developing and undeveloped countries. Asymmetric lifting task, combining lifting, bending and twisting motions of the torso, is more harmful to back spine than symmetric lifting task. Snook and Irvin 1) first developed the psychophysical approach to determine human maximum acceptable weight of lifting (MAWL) for preventing lifters from sustaining back injuries, and this approach has been adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
2
10
1
Order By: Relevance
“…Increasing lifting frequency from 1 lift/ min to 5 lifts/min resulted in 14% reduction in mean weight lifted compared to 47.1% found by Hafez (1984), and Hafez and Ayoub (1991), 23.5% found by Ramadan (1988), 16.1% found by Lee (2005) and 12.7% found by Singh et al (2012). The reason that Hafez (1984) has much higher reductions in MAWL than this study could be because the differences exist in the population employed, where in our study participants are used to and can tolerate more heat at work.…”
Section: Discussioncontrasting
confidence: 51%
“…Increasing lifting frequency from 1 lift/ min to 5 lifts/min resulted in 14% reduction in mean weight lifted compared to 47.1% found by Hafez (1984), and Hafez and Ayoub (1991), 23.5% found by Ramadan (1988), 16.1% found by Lee (2005) and 12.7% found by Singh et al (2012). The reason that Hafez (1984) has much higher reductions in MAWL than this study could be because the differences exist in the population employed, where in our study participants are used to and can tolerate more heat at work.…”
Section: Discussioncontrasting
confidence: 51%
“…The maximal acceptable weight (15% reduction from condition without lift asymmetry) for a lifting task with a 90° asymmetry was about one half of the RWL (30% reduction) determined by the RNLE (Han et al, 2005). These studies concluded that the RWL was more conservative in comparison with the results from the psychophysical studies (Han et al, 2005; Lee, 2005; Wu, 2003). …”
Section: Resultsmentioning
confidence: 95%
“…The assumption of psychophysical stress as an integration of physiological and biomechanical stress has been studied by several researchers1, 5, 8, 12 ) . Specific instructions were given for the MAWL determination to adjust the weight of the bag by adding or subtracting sand to the maximum amount that they could lift comfortably (i.e., without straining themselves) for an 8-h workday in an assigned task combination.…”
Section: Methodsmentioning
confidence: 99%
“…The maximum acceptable weight of lift (MAWL) is one of the most widely used approaches for representing a person’s lifting capacity and is thus employed to design appropriate jobs1 ) . When lifting, the weight and its distribution, shape, stiffness, and handles are object characteristics that must be considered in the design of lifting tasks2, 3 ) .…”
Section: Introductionmentioning
confidence: 99%